Nanoplastics in aquatic systems: challenges and advances in adsorptive removal technologies - Javed, Mahrosh; Lujanienė, Galina (Frontiers in Water, 2025)
Plastic pollution poses a major threat to both human health and ecosystems. This study investigates the formation and effects of nanoplastics (NPs) derived from the fragmentation and degradation of plastic waste. The study highlights adsorption as a promising method for the removal of NPs and emphasizes the development of adsorption materials such as biochar, sponges and aerogels. After a detailed overview of adsorption mechanisms, including hydrogen bonding, electrostatic attraction and pore filling, the study identifies key factors that influence adsorption performance, such as pH, pore size and adsorbent composition. It also discusses the challenges associated with adsorbent design, regeneration and environmental hazards, and encourages the development of biocompatible adsorbents and cost-effective solutions. The conclusions emphasize the urgent need to address the problem of NP pollution and provide a roadmap for future research and technological innovation in water treatment and environmental protection.